A new gene therapy approach by tenascin-c genome editing induces apoptosis and cell cycle arrest in triple- negative breast cancer cells - ÖZBAŞ, SUNA (My University, 2023)
BACKGROUND/AIMS: There is a pressing need for new therapies for the most aggressive subtype of breast cancer, triple-negative breast cancer (TNBC). Tenascin-C (TN-C) codes for a tumor microenvironment-specific protein, which promotes apoptosis evasion and cell proliferation. The aim of this study was to knock down TN-C by using the clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 system to induce cancer cell apoptosis and stunt cell proliferation, laying the grounds for a new gene therapy approach in TNBC.MATERIALS and METHODS: The human TNBC cell line, MDA-MB-231 cells were transfected by TN-C-specific CRISPR/Cas9 plasmids. TN-C messenger RNA levels were assessed by real-time polymerase chain reaction to determine the knock-down efficiency. Two days after the transfection, the percentage of apoptotic cells and the proportion of cells in cell cycle phases were compared between the treatment and the control groups using flow cytometry. The resultant change in cell proliferation due to the knock-down was determined by MTT assay. RESULTS: Transfection with the TN-C CRISPR/Cas9 plasmid reduced TN-C levels in the cells by approximately 49% relative to the scrambled -control CRISPR/Cas9 transfected cells. This TN-C downregulation increased the percentage of cells in apoptosis and induced G1-phase arrest. The combined effect of apoptosis and cell cycle arrest led to a significant decrease in the number of cancer cells in the treatment group.CONCLUSION: Our successful preliminary study of a potential TNBC gene therapy based on TN-C genome editing by the CRISPR/Cas9 system led to significant decrease in TNBC cell numbers and it justifies the testing of this system in more advanced preclinical studies.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Tenascin-C; CRISPR-cas systems; triple negative breast neoplasms; gene editing; apoptosis; PROLIFERATION; ACTIVATION; NICHE